Role of Service Innovation in Enhancing Customer Satisfaction in the Public Sector Organization - Handi Dipo Santosa (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research aims to explore the role of service innovation in enhancing customer satisfaction in the public sector organization in Indonesia. The research is conducted to address the lack of studies on the implementation of service innovation in the public sector organization in Indonesia, despite its importance in enhancing customer satisfaction. The study adopts a qualitative research approach, which involves collecting data from multiple sources, including interviews with service providers and customers, observations, and document analysis. The data collected were analyzed using content analysis to identify the themes and patterns. The findings of the study suggest that service innovation plays a crucial role in enhancing customer satisfaction in the public sector organization in Indonesia. Service innovation can improve the quality of service delivery, increase the efficiency of operations, and provide better customer experience. The study also identifies several factors that facilitate and hinder the implementation of service innovation, such as organizational culture, leadership support, and budget constraints.